A criatividade como um habitus regionalizado no campo artístico bourdieusiano - Jacques Haruo Fukushigue Jan-Chiba (Ciências Sociais Unisinos, 2017)
The artistic field is delimited by a discourse that imposes forms of interpreting, consecrat- ing and producing art according to the rules that have been imposed. This imposition is questioned, because it is not explicit who holds the power to authorize or name what art is. The producers of art are submissive to a field of force delimited by means of an artistic field’s regionalist speech. A device in the form of habitus becomes necessary, so that the artistic creation out of the dominant region’s limits has enough force of transformation through its factor of distinction. This device of distinction is creativity. As answer to the censorship imposed on creative action by means of dominant regionalist speeches, this article was developed with the objective of defending the creativity as a habitus of the artistic field. For that, we used Pierre Bourdieu’s theories of field (and more specifically, the artistic), symbolic power, region and habitus. It was concluded that the habitus theory represents the hidden side of the artistic goods market; that the struggles for a space in the artistic field are guerrillas among the artists themselves that seek for identity and reedom in the field and; that creativity as a habitus has several challenges in the artistic field, especially when delimited by a discourse.